Inflation in the world economy - Parkin Michael; Zis George (Manchester : Manchester University Press ; University of Toronto Press, 1976)
This volume brings together the papers presented at a conference of Inflation in the world economy in the University of Manchester from 17th July to 19 July 1974.
Includes bibliographical references and index.
osa 13/08/18
Loans
Keywords: Inflation (Finance).; Monetary policy .